1997
DOI: 10.1079/bjn19970140
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast: a review of associations with measures of dietary intake, physiology and biochemistry

Abstract: The present paper reviews the literature on breakfast to consider reported associations between breakfast and nutritional, physiological and biochemical variables. The contribution of breakfast to achieving nutrition targets for fat, carbohydrate and dietary fibre intakes is also examined as are the potential effects of fortified breakfast cereals on intakes of micronutrients and nutritional status. Breakfast consumption, particularly if the meal includes a breakfast cereal, is associated with lower intakes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
1
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(143 citation statements)
references
References 49 publications
8
128
1
6
Order By: Relevance
“…However, they have been unable to separate this from any metabolic effect that breakfast consumption may have (19,25,47) . The present study does not refute the suggestion that breakfast may be a marker of a healthy lifestyle since energy expenditure, activity levels and eating habits were primarily found to be independent of breakfast consumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, they have been unable to separate this from any metabolic effect that breakfast consumption may have (19,25,47) . The present study does not refute the suggestion that breakfast may be a marker of a healthy lifestyle since energy expenditure, activity levels and eating habits were primarily found to be independent of breakfast consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This can also in¯uence satiety and the eating patterns for the rest of the day . Increased consumption of a regular breakfast with a high carbohydrate intake has usually been considered as a healthy meal pattern (Ruxton & Kirk, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The results of recent studies indicated that a simple dietary intervention to increase the consumption of breakfast cereal led to a signi®cant reduction in the energy from fat and an increase in energy from carbohydrates (Gibson & O'Sullivan, 1995;Kirk et al, 1997;Ruxton & Kirk, 1997). It has been suggested, that plasma glucose values play an important role in the action on appetite .…”
Section: Introductionmentioning
confidence: 99%
“…Breakfast intake is considered an essential characteristic of a healthy diet pattern for adults and children, and has been found to correlate with attributes of a healthy lifestyle such as physical activity levels, cardiovascular health indices as well as cognitive and academic performance in youth (1)(2)(3) . With regard to the association of breakfast with diet quality in children and adolescents, it has been shown that those who regularly eat breakfast have a diet of higher overall quality (4,5) , better food choices, regular eating patterns (6)(7)(8) , consistent energy intake (6) , and nutrient and fibre intakes that are more likely to meet the recommended values (2,9) .…”
Section: Breakfast Intake Mediterranean Diet Obesity Serum Ironmentioning
confidence: 99%